HUMAN RESOURCES DEVELOPMENT IN A MODERN MANAGEMENT SYSTEM - Komiljon Baykhanov Olimjon o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article covers the theoretical and practical aspects of human resource development in a modern management system. Human capital development is analyzed as one of the main factors in increasing management efficiency and ensuring the competitiveness of organizations. Within the framework of the research, modern methods and technologies of human resource development are deeply studied, and innovative management mechanisms are proposed based on international best practices. Existing problems in human resource development are systematically analyzed, and scientific and practical recommendations are developed to eliminate them.